Erythrocyte antioxidative enzymes activities in patients with chronic hepatitis C treated with pegylated interferon alpha-2a and ribavirin - Popović Dragonjić, Lidija Dragoljub; Jovanović, Maja Vlastimir; Cvetković, Tatjana Petar; Vrbić, Miodrag Živojin; Kocić, Biljana Novica; Đorđević Spasić, Marina Milisav; Ranković, Aleksandar Žarko (Vojnosanitetski pregled, 2017)
Background/Aim. In hepatitis C virus infection, oxidative stress and antioxidant imbalance are major triggers for the disease occurrence and its progression. The aim of the research was to determine the erythrocyte antioxidative enzymes activities, superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT), before and after therapy with pegylated interferon alpha-2a and ribavirin and to evaluate their clinical significance as potential diagnostic markers of sustained virological response (SVR). Methods. The study included 53 patients with chronic hepatitis C (CHC) and 56 healthy controls. SOD, GPx, CAT, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were measured in patients both before and after the treatment. Results. SOD, GPx and CAT activities prior to the treatment were significantly lower in CHC patients  compared to the controls (p < 0.001), and they were  significantly higher after the treatment (p < 0.001). A significant positive correlation existed between SOD, GPx, and CAT activites, before and after the treatment (p < 0.001) and with those of aminotransferases prior to the treatment (p < 0.001). After the treatment, only GPx activity showed  significant negative correlation with that of aminotransferases (p < 0.001). Receiver operating characteristic curve analysis for SOD, GPx and CAT showed following values: area under the curve of 0.975, 0.988, and 0.817 respectively; sensitivity of 93.5%, 71.7%, 100% respectively and specificity of 100% for all, respectively. Forty six SVR achievers had significant increase of SOD, GPx and CAT activities (p < 0.001 for all), unlike 7 SVR non-achievers (p = 0.31, p = 0.717, p = 0.85, respectively). Conclusion. Oxidative stress is the initiator of onset and progression of  CHC.  The combined antiviral therapy leads to the restoration of antioxidant balance. GPx, SOD and CAT may be diagnostic markers of CHC treatment outcome.
Keywords: hepatitis c; erythrocytes; oxidative stress; antioxidants; superoxide dismutase; glutathione peroxidase; catalase; interferon-alpha; ribavirin